Optimisation of purification techniques for the preparation of large-volume aqueous solar nanoparticle inks for organic photovoltaics - Almyahi, Furqan; Andersen, Thomas R.; Cooling, Nathan A.; Holmes, Natalie P.; Griffith, Matthew J.; Feron, Krishna; Zhou, Xiaojing; Belcher, Warwick J.; Dastoor, Paul C. (Beilstein Journal of Nanotechnology, 2018)
In this study we have optimised the preparation conditions for large-volume nanoparticle inks, based on poly(3-hexylthiophene) (P3HT):indene-C60 multiadducts (ICxA), through two purification processes: centrifugal and crossflow ultrafiltration. The impact of purification is twofold: firstly, removal of excess sodium dodecyl sulfate (SDS) surfactant from the ink and, secondly, concentration of the photoactive components in the ink. The removal of SDS was studied in detail both by a UV–vis spectroscopy-based method and by surface tension measurements of the nanoparticle ink filtrate; revealing that centrifugal ultrafiltration removed SDS at a higher rate than crossflow ultrafiltration even though a similar filter was applied in both cases (10,000 Da Mw cut-off). The influence of SDS concentration on the aqueous solar nanoparticle (ASNP) inks was investigated by monitoring the surface morphology/topography of the ASNP films using atomic force microscopy (AFM) and scanning electron microscopy (SEM) and photovoltaic device performance as a function of ultrafiltration (decreasing SDS content). The surface morphology/topography showed, as expected, a decreased number of SDS crystallites on the surface of the ASNP film with increased ultrafiltration steps. The device performance revealed distinct peaks in efficiency with ultrafiltration: centrifuge purified inks reached a maximum efficiency at a dilution factor of 7.8 × 104, while crossflow purified inks did not reach a maximum efficiency until a dilution factor of 6.1 × 109. This difference was ascribed to the different wetting properties of the prepared inks and was further corroborated by surface tension measurements of the ASNP inks which revealed that the peak efficiencies for both methods occurred for similar surface tension values of 48.1 and 48.8 mN m−1. This work demonstrates that addressing the surface tension of large-volume ASNP inks is key to the reproducible fabrication of nanoparticle photovoltaic devices.
Keywords: aqueous nanoparticle; crossflow ultrafiltration; miniemulsion; organic photovoltaic; SDS surfactant; surface tension